Cupric porphyrin frameworks on multi-junction silicon photocathodes to expedite the kinetics of CO2 turnover. Issue 25 (20th June 2022) - Wei, Zhihe; Mu, Qiaoqiao; Fan, Ronglei; Su, Yanhui; Lu, Yongtao; Deng, Zhao; Shen, Mingrong; Peng, Yang
Abstract : The 3D porous Cu-TCPP(Cu) MOF was adopted as the catalytic scaffold on exquisite multi-junction Si-based photocathodes for boosting both the kinetics and selectivity of photoelectrochemical CO2 reduction reactions. Abstract : Photoelectrochemical CO2 reduction utilizing silicon-based photocathodes offers a promising route to directly store solar energy in chemical bonds, provoking the development of heterogeneous molecular catalysts with high turnover rates. Herein, an in situ surface transformation strategy is adopted to grow metal–organic frameworks (MOFs) on Si-based photocathodes, serving as catalytic scaffolds for boosting both the kinetics and selectivity of CO2 reduction. Benefitting from the multi-junctional configuration for enhanced charge separation and the porous MOF scaffold enriching redox-active metalloporphyrin sites, the Si photocathode demonstrates a high CO faradaic efficiency of 87% at a photocurrent density of 10.2 mA cm −2, which is among the best seen for heterogeneous molecular catalysts. This study highlights the exploitation of reticular chemistry and macrocycle complexes as Earth-abundant alternatives for catalyzing artificial photosynthesis.